Do Public Program Benefits Crowd Out Private Transfers in Developing Countries? A Critical Review of Recent Evidence - Plamen Nikolov; Matthew Bonci (Institute of Labor Economics (IZA), 2020)
Precipitated by rapid globalization, rising inequality, population growth, and longevity gains, social protection programs have been on the rise in low- and middle-income countries (LMICs) in the last three decades. However, the introduction of public benefits could displace informal mechanisms for risk-protection, which are especially prevalent in LMICs. If the displacement of private transfers is considerably large, the expansion of social protection programs could even lead to social welfare loss. In this paper, we critically survey the recent empirical literature on crowd-out effects in response to public policies, specifically in the context of LMICs. We review and synthesize patterns from the behavioral response to various types of social protection programs. Furthermore, we specifically examine for heterogeneous treatment effects by important socioeconomic characteristics. We conclude by drawing on lessons from our synthesis of studies. If poverty reduction objectives are considered, along with careful program targeting that accounts for potential crowd-out effects, there may well be a net social gain.
Keywords: D64; H31; H55; J14; J22; J26; O15; O16; R2; 330; life cycle; retirement; social protection; developing countries; crowd-out effect; inter vivos transfers